Modern approaches to diagnostics and treatment of migraine in children - Kovalchuk, P V; Katilov, O V; Panenko, S O (Pain medicine, 2019)
This article reviews modern approaches to diagnostics and treatment of a very common and simultaneously underestimated and often maltreated disorder in children. It is fallacious management of migraine masked behind the diagnoses such as autonomic vessel dysfunction and vascular headache here in Ukraine. This is a tremendous problem and it should be solved with appropriate information spread across the medical community. Up-to-date classification according to the International Headache Society, diagnostic criteria, differential diagnosis, investigation and treatment strategies are presented in the article. All supported data are com-pliant with guidelines of developed countries with evidence-based medicine (US, Canada, Great Britain, Japan, Australia, New Zealand) enhanced with new trials and approved methods. Migraine management is a rapidly evolving concept, where major changes were done during recent years (transcranial Deep Brain Stimulation, vagus stimulation, CGRP-receptor mono-clonal antibodies). Considering disorder incidence and its impact on life quality and the existence of options for alleviating symptoms, this information is important for physicians who work with children, especially for general practitioners, pediatrics, pediatric and adult neurologists.